Constituents, properties and clinical applications of OrthoMTA & RetroMTA: A systematic review - Viral Maru; Uma B Dixit (Wolters Kluwer Medknow Publications, 2021)
Aim: OrthoMTA and RetroMTA are newly developed mineral trioxide aggregates that were developed to achieve maximum benefits and clinical performance. This systematic review aimed at assessing and describing the constituents, properties and uses of OrthoMTA and RetroMTA. Methodology: Literature search was performed using the keywords, "OrthoMTA", "RetroMTA", "BioMTA", "constituents" and "properties" in the databases, PubMed, Cochrane, Semantic scholar and Europe PubMed Central. Original articles in English describing the properties, constituents, uses/indications, history and recent advances on OrthoMTA and RetroMTA were considered for the study. Results: A total of 35 articles were selected for the systematic review based on keywords selected. Among the 35 articles, 5 articles described the composition and properties of OrthoMTA and RetroMTA, 7 articles depicted the usage of OrthoMTA and RetroMTA and the remaining articles discussed on the various properties of both OrthoMTA and RetroMTA. Conclusion: The present review confirmed that RetroMTA exhibits an excellent property, namely, short setting time, less tooth discoloration, high compressive strength, higher shear bond strength with time, higher push-out bond strength, low solubility, low cytotoxicity, biocompatibility, antibacterial property, and can be used in reparative processes in case of blood contamination. However, even OrthoMTA showed less microleakage, is biocompatible and possesses antibacterial properties.